Growth of a solitary pulmonary nodule after 6 years diagnosed as oncocytic carcinoid tumour with a high 18‐fluorodeoxyglucose (18F‐FDG) uptake in positron emission tomography‐computed tomography (PET‐CT). (16th January 2012) - Turan, Onur; Ozdogan, Ozhan; Gurel, Duygu; Onen, Ahmet; Kargi, Aydanur; Sevinc, Can
Abstract Introduction: Pulmonary carcinoid tumour is low‐grade neuroendocrine malignancy that is seen 1%–2% of all lung neoplasms. Oncocytic carcinoid type is a rarely seen variant of pulmonary carcinoids. As carcinoid tumours have hypometabolic activity, they usually have lower 18‐fluorodeoxyglucose (18F‐FDG) uptake than expected for lung carcinoma on positron emission tomography (PET). Case Report: A 45‐year‐old non‐smoking man had a stable solitary pulmonary nodule followed for 6 years; the tumour remained the same size (1.5 × 2.4 cm) during this period. The patient was admitted to the hospital with complaints of repetitive sneezing and rhinorrhoea. He also experienced flushing and bronchospasm. His chest X‐ray revealed a minimal increase in the size of the solitary pulmonary nodule (2.0 × 2.8 cm). In PET‐computed tomography (CT), the parenchymal nodule in the anterior segment of the right lung had a standard uptake value of 38.0 mg/mL, which was interpreted as a malignant nodule. He underwent fibre‐optic bronchoscopy, but cytology showed no evidence of malignancy. Right upper and middle bilobectomy was performed, and a pulmonary carcinoid tumour with an oncocytic subgroup was diagnosed. The diagnosis of carcinoid syndrome was further confirmed by an elevated 24‐h urinary excretion of 5‐hydroxyindoleacetic acid. Conclusion: We present a rare case of an oncocytic carcinoid tumour with an increase in the size of a solitary pulmonary nodule after 6 years' follow‐up. In addition, PET‐CT showed a very high 18F‐FDG uptake in this patient, which is an unexpected finding with a pulmonary carcinoid tumour. Please cite this paper as: Turan O, Ozdogan O, Gurel D, Onen A, Kargi A and Sevinc C. Growth of a solitary pulmonary nodule after 6 years diagnosed as oncocytic carcinoid tumour with a high 18F‐FDG uptake in positron emission tomography‐computed tomography (PET‐CT). Clin Respir J 2013; 7: e1–e5.